Pengaruh Penerapan Keselamatan dan Kesehatan Kerja (K3), Pengawasan dan Disiplin Kerja terhadap Kinerja Karyawan di PO.Cipta Karya Mandiri Tugumulyo - Surajiyo Surajiyo; Rudi Azhar; Muhammat Fatdly (Journal Social Society, 2026)
Employee performance is an important factor in maintaining productivity, product quality, and operational sustainability. At PO. Cipta Karya Mandiri Tugumulyo, several employees were still unable to achieve the predetermined work targets, resulting in decreased output, defective products, cutting errors, and finishing results that did not meet specifications. This condition indicates the urgency of examining factors that may influence employee performance, particularly Occupational Safety and Health (OHS), supervision, and work discipline. This study aimed to determine the effect of OHS, supervision, and work discipline, both partially and simultaneously, on employee performance at PO. Cipta Karya Mandiri Tugumulyo. This research used a quantitative approach. The population consisted of all employees of PO. Cipta Karya Mandiri Tugumulyo, with a total sample of 47 respondents selected using a saturated sampling technique. Data were collected through questionnaires and analyzed using t-tests and F-tests. The results showed that OHS had a significant effect on employee performance, with a t-count value of 2.211 greater than the t-table value of 1.671. Supervision also had a significant effect on employee performance, with a t-count value of 5.177 greater than the t-table value of 1.671. Furthermore, work discipline had a significant effect on employee performance, with a t-count value of 4.615 greater than the t-table value of 1.671. Simultaneously, OHS, supervision, and work discipline affected employee performance, as indicated by an F-count value of 7.525 greater than the F-table value of 2.53. These findings imply that improving OHS implementation, strengthening supervision, and enhancing work discipline are essential strategies for improving employee performance.